Management of Cleft Lip and Palate (Literature Review) - Putu Sulistiawati Dewi (Faculty of Dentistry, Mahasaraswati Denpasar University, 2019)
Cleft lip and cleft palate (orofacial cleft) are facial and oral malformations that occur very early in pregnancy. A cleft lip and cleft palate, known technically as an orofacial cleft, is actually a group of various conditions that involve a ‘cleft” on the patient’s face. Clefting results when there is not enough tissue in the mouth or lip area, and the tissue that is available does not join together properly. Cleft lip and cleft palate can occur on one or both sides of the mouth. Because the lip and the palate develop separately, it is possible to have a cleft lip without a cleft palate, a cleft palate without a cleft lip, or both together. Children with a cleft lip with or without a cleft palate or a cleft palate alone often have problems with feeding and speaking clearly and can have ear infections. They also might have hearing problems and problems with their teeth. Cleft lip with or without cleft palate, can be diagnosed during pregnancy by a routine ultrasound. They can also be diagnosed after the baby is born, especially cleft palate. Treatment with orofacial clefts can vary depending on the severity of the cleft; the child’s age and needs; and the presence of associated syndromes or other birth defects, or both.